2017
DOI: 10.1167/iovs.17-22166
|View full text |Cite
|
Sign up to set email alerts
|

Does Decreased Static Ocular Counter Rolling Account for Bielschowsky Head Tilt Test in Unilateral Superior Oblique Palsy?

Abstract: PURPOSE. To understand the relationship of static ocular counter rolling (s-OCR) and clinical manifestations in acquired unilateral superior oblique palsy subjects during the Bielschowsky head tilt test.METHODS. Nineteen subjects that were diagnosed with acquired unilateral superior oblique palsy were included. Fundus photographs were obtained at different head tilt angles to evaluate static ocular counter rolling using a fundus camera with a cervical range of motion device. Using a graphics editing program, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…While obtaining fundus photographs, the examiner held each subject’s head and watched the CROM angle to make sure subjects were maintaining the correct angle. The detailed methodology for these measurements has been described in our previous studies [8]. The postoperative fundus photographs were obtained at least 3 months after the surgery.…”
Section: Methodsmentioning
confidence: 99%
“…While obtaining fundus photographs, the examiner held each subject’s head and watched the CROM angle to make sure subjects were maintaining the correct angle. The detailed methodology for these measurements has been described in our previous studies [8]. The postoperative fundus photographs were obtained at least 3 months after the surgery.…”
Section: Methodsmentioning
confidence: 99%
“…No previous studies have directly addressed the fundus torsional state of both eyes in acquired USOP patients. Choi et al [11] reported DFAs of paretic (12.67°) and non-paretic (9.59°) eyes in 22 acquired USOP patients. Lee et al [4] reported that fundus torsional states were present in 61% of the paretic eyes of 31 acquired USOP patients.…”
Section: Discussionmentioning
confidence: 99%
“…17 Most fundus photography methods measure ocular torsion with the head and eyes in a static posture. 18,19 However, it is difficult to measure ocular torsion using a dynamic posture or fixation distance. If a patient’s pupil is extremely small, pharmacologic dilation or dark adaptation approaches may be necessary; cataracts may also cause measurement difficulty.…”
Section: Introductionmentioning
confidence: 99%